O uso de dados pessoais e a segurança pública: perspectivas práticas e teóricas da regulação no Brasil - Lazzaretti, Bianca Kaini (Universidade do Vale do Rio dos Sinos, 2022)
In a context of rapid technological evolution, hyperconnected, the amount of personal data available and the possibilities of its use are unprecedented. Several practices already apply technologies to analyze these data under the justification of criminal prevention and repression. With the need to reconcile the fundamental rights to personal data protection and public safety, some proposals for regulation of the theme have stood out - the main one being Bill no. 1.515, of 2022, presented to the House of Representatives of Brazil. In this sense, the present work is driven by the following research question: to what extent does the proposed criminal LGPD (Bill No. 1.515 of 2022) limit and guarantee the fundamental right to the protection of personal data within the context of ensuring public security in a broad sense? To answer this, the research used the systemic-constructivist method. The dissertation is divided into two parts: the first, exploratory, aims to conceptualize and identify personal data and possible uses in the criminal sphere; the second, descriptive, seeks to define the colliding fundamental rights, with the identification of the possibilities of restriction and the "limit to the limits" imposed by one right over the other. We conclude that the Bill no. 1.515/2022 overvalues public security, invading the essential core of the fundamental right to the protection of personal data, limiting the latter right rather than guaranteeing it.
Keywords: Proteção de dados pessoais; Segurança pública; LGPD; Direito constitucional; Personal data protection; Public safety; GDPR; Constitutional law; ACCNPQ::Ciências Sociais Aplicadas::Direito